Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Metallic and semiconducting nanoparticles in LCs - Sharma, Anshul; Urbanski, Martin; Mori, Taizo; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Series in Soft Condensed Matter)

Influence of Proton and Salt Concentration on the Chromonic Liquid Crystal Phase Diagram of Disodium Cromoglycate Solutions: Prospects and Limitations of a Host for DNA Nanostructures - Zhang, Bingru; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Alignment and Graphene-Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva-Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz-Siegfried (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Quantum interference control of electrical currents in GaAs microstructures: physics and spectroscopic applications - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Thunich, S.; Duc, H. T.; Podzimski, R.; Meier, Torsten; Betz, M. (Applied Physics B)

Indium oxide inverse opal films synthesized by structure replication method - Amrehn, Sabrina; Berghoff, Daniel; Nikitin, Andreas; Reichelt, Matthias; Wu, Xia; Meier, Torsten; Wagner, Thorsten (Photonics and Nanostructures - Fundamentals and Applications)
We present the synthesis of indium oxide (In2O3) inverse opal films with photonic stop bands in the visible range by a structure replication method. Artificial opal films made of poly(methyl methacrylate) (PMMA) spheres are utilized as template. The opal films are deposited via sedimentation facilitated by ultrasonication, and then impregnated by indium nitrate solution, which is thermally converted to In2O3 after drying. The quality of the resulting inverse opal film depends on many parameters; in this study the water content of the indium nitrate/PMMA composite after drying is investigated. Comparison of the reflectance spectra recorded by vis-spectroscopy with simulated data shows a good agreement between the peak position and calculated stop band positions for the inverse opals. This synthesis is less complex and highly efficient compared to most other techniques and is suitable for use in many applications.

Dynamics of dipoles and vortices in nonlinearly coupled three-dimensional field oscillators - Driben, R.; Konotop, V. V.; Malomed, B. A.; Meier, Torsten (Physical Review E)
The dynamics of a pair of harmonic oscillators represented by three-dimensional fields coupled with a repulsive cubic nonlinearity is investigated through direct simulations of the respective field equations and with the help of the finite-mode Galerkin approximation (GA), which represents the two interacting fields by a superposition of 3+3 harmonic-oscillator p-wave eigenfunctions with orbital and magnetic quantum numbers l=1 and m=1, 0, −1. The system can be implemented in binary Bose-Einstein condensates, demonstrating the potential of the atomic condensates to emulate various complex modes predicted by classical field theories. First, the GA very accurately predicts a broadly degenerate set of the system's ground states in the p-wave manifold, in the form of complexes built of a dipole coaxial with another dipole or vortex, as well as complexes built of mutually orthogonal dipoles. Next, pairs of noncoaxial vortices and/or dipoles, including pairs of mutually perpendicular vortices, develop remarkably stable dynamical regimes, which feature periodic exchange of the angular momentum and periodic switching between dipoles and vortices. For a moderately strong nonlinearity, simulations of the coupled-field equations agree very well with results produced by the GA, demonstrating that the dynamics is accurately spanned by the set of six modes limited to l=1.

Photocurrents in semiconductors and semiconductor quantum wells analyzed by k.p-based Bloch equations - Podzimski, Reinold; Duc, Huynh Thanh; Priyadarshi, Shekhar; Schmidt, Christian; Bieler, Mark; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XX)

Advanced optical manipulation of carrier spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Meier, Torsten; Zrenner, Artur; Bayer, M. (Applied Physics B)
Spins in semiconductor quantum dots have been considered as prospective quantum bit excitations. Their coupling to the crystal environment manifests itself in a limitation of the spin coherence times to the microsecond range, both for electron and hole spins. This rather short-lived coherence compared to atomic states asks for manipulations on timescales as short as possible. Due to the huge dipole moment for transitions between the valence and conduction band, pulsed laser systems offer the possibility to perform manipulations within picoseconds or even faster. Here, we report on results that show the potential of optical spin manipulations with currently available pulsed laser systems. Using picosecond laser pulses, we demonstrate optically induced spin rotations of electron and hole spins. We further realize the optical decoupling of the hole spins from the nuclear surrounding at the nanosecond timescales and demonstrate an all-optical spin tomography for interacting electron spin sub-ensembles.
Keywords: Spin Polarization; Pump Pulse; Trion; Spin Component; Coherence Time

Two-dimensional symbiotic solitons and vortices in binary condensates with attractive cross-species interaction - Ma, Xuekai; Driben, Rodislav; Malomed, Boris A.; Meier, Torsten; Schumacher, Stefan (Scientific Reports)

Ultrafast shift and rectification photocurrents in GaAs quantum wells: Excitation intensity dependence and the importance of band mixing - Duc, Huynh Thanh; Podzimski, Reinold; Priyadarshi, Shekhar; Bieler, Mark; Meier, Torsten (Physical Review B)
A microscopic approach that is based on the multisubband semiconductor Bloch equations formulated in the basis of a 14-band k⋅p model is employed to compute the temporal dynamics of photocurrents in GaAs quantum wells following excitation with femtosecond laser pulses. This approach provides a transparent description of the interband, intersubband, and intraband excitations, fully includes all resonant as well as off-resonant excitations, and treats the light-matter interaction nonperturbatively. For linearly polarized excitations, the photocurrents contain contributions from shift and rectification currents. We numerically compute and analyze these currents generated by excitation with femtosecond laser pulses for [110]- and [111]-oriented GaAs quantum wells. It is shown that the often employed perturbative χ(2) approach breaks down for peak fields larger than about 10 kV/cm, and that nonperturbative effects lead to a reduction of the peak values of the shift and rectification currents and to temporal oscillations that originate from Rabi flopping. In particular, we find a complex oscillatory photon energy dependence of the magnitudes of the shift and rectification currents. Our simulations demonstrate that this dependence is the result of mixing between the heavy- and light-hole valence bands. This is a surprising finding since the band mixing has an even larger influence on the strength of the photocurrents than the absorption coefficient. For [110]-oriented GaAs quantum wells, the calculated photon energy dependence is compared to experimental results, and good agreement is obtained. This validates our theoretical approach.

Precession and nutation dynamics of nonlinearly coupled non-coaxial three-dimensional matter wave vortices - Driben, R.; Konotop, V. V.; Meier, Torsten (Scientific Reports)
Nonlinearity is the driving force for numerous important effects in nature typically showing transitions between different regimes, regular, chaotic or catastrophic behavior. Localized nonlinear modes have been the focus of intense research in areas such as fluid and gas dynamics, photonics, atomic and solid state physics etc. Due to the richness of the behavior of nonlinear systems and due to the severe numerical demands of accurate three-dimensional (3D) numerical simulations presently only little knowledge is available on the dynamics of complex nonlinear modes in 3D. Here, we investigate the dynamics of 3D non-coaxial matter wave vortices that are trapped in a parabolic potential and interact via a repulsive nonlinearity. Our numerical simulations demonstrate the existence of an unexpected and fascinating nonlinear regime that starts immediately when the nonlinearity is switched-on and is characterized by a smooth dynamics representing torque-free precession with nutations. The reported motion is proven to be robust regarding various effects such as the number of particles, dissipation and trap deformations and thus should be observable in suitably designed experiments. Since our theoretical approach, i.e., coupled nonlinear Schrödinger equations, is quite generic, we expect that the obtained novel dynamical behavior should also exist in other nonlinear systems.

Ultrafast dynamical response of the lower exciton-polariton branch in CdZnTe - Lohrenz, J.; Melzer, S.; Ruppert, C.; Akimov, I. A.; Mariette, H.; Reichelt, Matthias; Trautmann, Alexander; Meier, Torsten; Betz, M. (Physical Review B)
We investigate the transient optical response in high-quality Cd0.88Zn0.12Te crystals in the regime of slow light propagation on the lower exciton-polariton branch. Femtosecond photoexcitation leads to very substantial transmission changes in a ∼10-meV broad spectral range within the transparency window of the unexcited semiconductor. These nonlinear optical signatures decay on picosecond time scales governed by carrier thermalization and recombination. The temporal and spectral dependence indicate the dynamical optical response as arising from excitation-induced dephasing and perturbed free induction decay. Model simulations for the optical response taking into account the actual exciton-polariton dispersion and excitation-induced dephasing of a nonlinearly driven two-level system support this interpretation.

Identification of ferroelectric domain structure sensitive phonon modes in potassium titanyl phosphate: A fundamental study - Rüsing, Michael; Eigner, Christof; Mackwitz, P.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)
Confocal Raman spectroscopy is applied to identify ferroelectric domain structure sensitive phonon modes in potassium titanyl phosphate. Therefore, polarization-dependent measurements in various scattering configurations have been performed to characterize the fundamental Raman spectra of the material. The obtained spectra are discussed qualitatively based on an internal mode assignment. In the main part of this work, we have characterized z-cut periodically poled potassium titanyl phosphate in terms of polarity- and structure-sensitive phonon modes. Here, we find vibrations whose intensities are linked to the ferroelectric domain walls. We interpret this in terms of changes in the polarizability originating from strain induced by domain boundaries and the inner field distribution. Hence, a direct and 3D visualization of ferroelectric domain structures becomes possible in potassium titanyl phosphate.

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Periodic domain inversion in x-cut single-crystal lithium niobate thin film - Mackwitz, P.; Rüsing, Michael; Berth, Gerhard; Widhalm, A.; Müller, K.; Zrenner, Artur (Applied Physics Letters)
We report the fabrication of periodically poled domain patterns in x-cut lithium niobate thin-film. Here, thin films on insulator have drawn particular attention due to their intrinsic waveguiding properties offering high mode confinement and smaller devices compared to in-diffused waveguides in bulk material. In contrast to z-cut thin film lithium niobate, the x-cut geometry does not require back electrodes for poling. Further, the x-cut geometry grants direct access to the largest nonlinear and electro-optical tensor element, which overall promises smaller devices. The domain inversion was realized via electric field poling utilizing deposited aluminum top electrodes on a stack of LN thin film/SiO2 layer/Bulk LN, which were patterned by optical lithography. The periodic domain inversion was verified by non-invasive confocal second harmonic microscopy. Our results show domain patterns in accordance to the electrode mask layout. The second harmonic signatures can be interpreted in terms of spatially, overlapping domain filaments which start their growth on the þz side.

Joint Raman spectroscopy and HRXRD investigation of cubic gallium nitride layers grown on 3C-SiC - Rüsing, Michael; Wecker, T.; Berth, Gerhard; As, Donat Josef; Zrenner, Artur (physica status solidi (b))
Cubic gallium nitride (GaN) films are analyzed with highresolution X-ray diffraction (HRXRD) and Raman spectroscopy. Several cubic GaN layers were grown on 3C-SiC (001) substrate by radio-frequency plasma-assisted molecular beam epitaxy. The layer thickness of the cubic GaN was varied between 75 and 505 nm. The HRXRD analysis reveals a reduction of the full-width at half-maximum (FWHM) of omega scans for growing layer thicknesses, which is caused by a partial compensation of defects. The Raman characterization confirms well-formed c-GaN layers. A more detailed examination of the longitudinal optical mode hints at a correlation of the FWHM of the Raman mode with the dislocation density, which shows the possibility to determine dislocation densities by Ramanspectroscopy on a micrometer scale, which is not possible by HRXRD. Furthermore, this Raman analysis shows that normalized Raman spectra present an alternative way to determine layer thicknesses of thin GaN films.
Keywords: cubic gallium nitride; dislocation density; HRXRD; Raman spectroscopy

Vibrational properties of LiNb1−xTaxO3 mixed crystals - Rüsing, Michael; Sanna, Simone; Neufeld, Sergej; Berth, Gerhard; Schmidt, Wolf Gero; Zrenner, Artur; Yu, H.; Wang, Y.; Zhang, H. (Physical Review B)
Congruent lithium niobate and lithium tantalate mixed crystals have been grown over the complete compositional range with the Czochralski method. The structural and vibrational properties of the mixed crystals are studied extensively by x-ray diffraction measurements, Raman spectroscopy, and density functional theory. The measured lattice parameters and vibrational frequencies are in good agreement with our theoretical predictions. The observed dependence of the Raman frequencies on the crystal composition is discussed on the basis of the calculated phonon displacement patterns. The phononic contribution to the static dielectric tensor is calculated by means of the generalized Lyddane-Sachs-Teller relation. Due to the pronounced dependence of the optical response on the Ta concentration, lithium niobate tantalate mixed crystals represent a perfect model system to study the properties of uniaxial mixed ferroelectric materials for application in integrated optics.

Spatially indirect transitions in electric field tunable quantum dot diodes - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk (physica status solidi (b))

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Nuclear spin polarization in the electron spin-flip Raman scattering of singly charged (In,Ga)As/GaAs quantum dots - Debus, J.; Kudlacik, D.; Sapega, V. F.; Dunker, D.; Bohn, P.; Paßmann, F.; Braukmann, D.; Rautert, J.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transform-limited single photons from a single quantum dot - Kuhlmann, Andreas V.; Prechtel, Jonathan H.; Houel, Julien; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Nature Communications)

Influence of Post-Implantation Annealing Parameters on the Focused Ion Beam Directed Nucleation of InAs Quantum Dots - Mehta, M.; Reuter, Dirk; Kamruddin, M.; Tyagi, A. K.; Wieck, A. D. (Nano)

Fabrication and characterisation of gallium arsenide ambipolar quantum point contacts - Chen, J. C. H.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Trunov, K.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Extending the spectral range of CdSe/ZnSe quantum wells by strain engineering - Finke, A.; Ruth, M.; Scholz, S.; Ludwig, A.; Wieck, A. D.; Reuter, Dirk; Pawlis, A. (Physical Review B)

Spatially indirect transitions in electric field tunable quantum dot diodes - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk (physica status solidi (b))
We analyse an InAs/GaAs-based electric ﬁeld tunable single quantum dot diode with a thin tunnelling barrier between a buried n þ -back contact and a quantum dot layer. In voltage- dependent photoluminescence measurements, we observe rich signatures from spatially direct and indirect transitions from the wetting layer and from a single quantum dot. By analysing the Stark effect, we show that the indirect transitions result from a recombination between conﬁned holes in the wetting or quantum dot layer with electrons from the edge of the Fermi sea in the back contact. Using a 17 nm tunnel barrier which provides comparably weak tunnel coupling allowed us to observe clear signatures of direct and corresponding indirect lines for a series of neutral and positively charged quantum dot states.
Keywords: excitons; GaAs; InAs; quantum dots; spatially indirect transitions; Stark shift

A quantum dot single-photon source with on-the-fly all-optical polarization control and timed emission - Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Schumacher, Stefan (Nature Communications)
Sources of single photons are key elements for applications in quantum information science. Among the different sources available, semiconductor quantum dots excel with their integrability in semiconductor on-chip solutions and the potential that photon emission can be triggered on demand. Usually, the photon is emitted from a single-exciton ground state. Polarization of the photon and time of emission are either probabilistic or pre-determined by electronic properties of the system. Here, we study the direct two-photon emission from the biexciton. The two-photon emission is enabled by a laser pulse driving the system into a virtual state inside the band gap. From this intermediate state, the single photon of interest is then spontaneously emitted. We show that emission through this higher-order transition provides a versatile approach to generate a single photon. Through the driving laser pulse, polarization state, frequency and emission time of the photon can be controlled on-the-fly.

Photonic crystal cavities with metallic Schottky contacts - Quiring, W.; Al-Hmoud, M.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Applied Physics Letters)
We report about the fabrication and analysis of high Q photonic crystal cavities with metallic Schottky-contacts. The structures are based on GaAs n-i membranes with an InGaAs quantum well in the i-region and nanostructured low ohmic metal top-gates. They are designed for photocurrent readout within the cavity and fast electric manipulations. The cavity structures are characterized by photoluminescence and photocurrent spectroscopy under resonant excitation. We find strong cavity resonances in the photocurrent spectra and surprisingly high Q-factors up to 6500. Temperature dependent photocurrent measurements in the region between 4.5K and 310K show an exponential enhancement of the photocurrent signal and an external quantum efficiency up to 0.26.

Stochastic pumping of a polariton fluid - Assmann, Marc; Bayer, Manfred (PHYSICAL REVIEW A)
We investigate the response of a polariton laser driven slightly off-resonantly using light fields differing from the routinely studied coherent pump sources. The response to driving light fields with thermal and displaced thermal statistics with varying correlation times shows significant differences in the transmitted intensity, its noise, and the position of the nonlinear threshold. We predict that adding more photons on average may actually reduce the transmission through the polariton system.

Electric field effect on optical harmonic generation at the exciton resonances in GaAs - Brunne, D.; Lafrentz, M.; Pavlov, V. V.; Pisarev, R. V.; Rodina, A. V.; Yakovlev, D. R.; Bayer, M. (Physical Review B)
An electric field applied to a semiconductor reduces its crystal symmetry and modifies its electronic structure which is expected to result in changes of the linear and nonlinear response to optical excitation. In GaAs, we observe experimentally strong electric field effects on the optical second (SHG) and third (THG) harmonic generation. The SHG signal for the laser-light k vector parallel to the [001] crystal axis is symmetry forbidden in the electric-dipole approximation, but can be induced by an applied electric field in the vicinity of the 1s exciton energy. Surprisingly, the THG signal, which is allowed in this geometry, is considerably reduced by the electric field. We develop a theory which provides good agreement with the experimental data. In particular, it shows that the optical nonlinearities for the 1s exciton resonance are modified in an electric field by the Stark effect, which mixes the 1s and 2p exciton states of opposite parity. This mixing acts in opposite way on the SHG and THG processes, as it leads to the appearance of forbidden SHG in (001)-oriented GaAs and decreases the crystallographic THG.

Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Novel mechanisms of optical harmonic generation on excitons in semiconductors - Yakovlev, D. R.; Warkentin, W.; Brunne, D.; Mund, J.; Pavlov, V. V.; Rodina, A. V.; Pisarev, R. V.; Bayer, M. (Nonlinear Optics and Applications IX)

Nonlinear optical sub-bandgap excitation of ZnO-based photonic resonators - Bader, Christina A.; Zeuner, Franziska; Bader, Manuel H. W.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

Broadband Hybrid Holographic Multiplexing with Geometric Metasurfaces - Huang, Lingling; Mühlenbernd, Holger; Li, Xiaowei; Song, Xu; Bai, Benfeng; Wang, Yongtian; Zentgraf, Thomas (Advanced Materials)

Continuous control of the nonlinearity phase for harmonic generations - Li, Guixin; Chen, Shumei; Pholchai, Nitipat; Reineke, Bernhard; Wong, Polis Wing Han; Pun, Edwin Yue Bun; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nature Materials)

Metasurface holograms reaching 80% efficiency - Zheng, Guoxing; Mühlenbernd, Holger; Kenney, Mitchell; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nature Nanotechnology)

Amplitude- and Phase-Controlled Surface Plasmon Polariton Excitation with Metasurfaces - Mühlenbernd, Holger; Georgi, Philip; Pholchai, Nitipat; Huang, Lingling; Li, Guixin; Zhang, Shuang; Zentgraf, Thomas (ACS Photonics)

Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Silicon photonics 90° optical hybrid design for coherent receivers - Gudyriev, Sergiy; Scheytt, Christoph (Kleinheubacher Tagung 2015)
The recent rapid development of silicon photonics technology has spurred the process of on-chip integration of all kinds of opto-electronic components. One of the most common components of such type is the opto-electrical receiver. The monolithic implementation of the receiver could potentially have lower power consumption, higher sensitivity and bandwidth due to very short diode to amplifier connection length, which has very low parasitic capacitance and series resistance. The SiGe photodiode itself is also very compact, thus lowering the junction capacitance and improving its bandwidth. Among the different optical communication systems, coherent transmission lately received a lot of attention due to the rising requirements of the optical link capacity, and it was shown that this particular approach could benefit greatly from the monolithic integration, since the major component required for the demodulation on the receiver side – 90° optical hybrid – could be implemented fully passive and directly on the same chip as the receiver itself, together with digital post-processing circuitry. Despite the initial complexity of the modulation scheme, advanced silicon photonics components like this optical hybrid could make coherent transmission attractive even for short-range optical links. I would like to present the actual designs, implementation and measurement results of 90° fully passive optical hybrids, implemented in the IHP SG25PIC (passive photonics IC) technology. One of the designs is based on 4x4 multimode interferometer (MMI). The other one is based on two separate 2x2 MMIs with additional delay element. The final designs didn’t require any additional tuning after fabrication and have shown sufficient precision and performance for a coherent system design. The results of this work were later used for the design of monolithic coherent receiver.

Self-organized assemblies of colloidal particles obtained from an aligned chromonic liquid crystal dispersion - Zimmermann, Natalie; Jünnemann-Held, Gisela; Collings, Peter J.; Kitzerow, Heinz-Siegfried (Soft Matter)
Keywords: Condensed Matter Physics; General Chemistry

Chemically and thermally stable, emissive carbon dots as viable alternatives to semiconductor quantum dots for emissive nematic liquid crystal–nanoparticle mixtures with lower threshold voltage - Urbanski, Martin; Mirzaei, Javad; Sharma, Anshul; Hofmann, Daniel; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Electrically tunable zero dispersion wavelengths in photonic crystal fibers filled with a dual frequency addressable liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Storage of hyperentanglement in a solid-state quantum memory - Tiranov, Alexey; Lavoie, Jonathan; Ferrier, Alban; Goldner, Philippe; Verma, Varun B.; Nam, Sae Woo; Mirin, Richard P.; Lita, Adriana E.; Marsili, Francesco; Herrmann, Harald; Silberhorn, Christine; Gisin, Nicolas; et al. (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (SPIE Proceedings Vol. 9361: Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Raman scattering efficiency in LiTaO3 and LiNbO3 crystals - Sanna, Simone; Neufeld, Sergej; Rüsing, Michael; Berth, Gerhard; Zrenner, Artur; Schmidt, Wolf Gero (Physical Review B)
LiTaO3 and LiNbO3 crystals are investigated here in a combined experimental and theoretical study that uses Raman spectroscopy in a complete set of scattering geometries and corresponding density-functional theory calculations to provide microscopic information on their vibrational properties. The Raman scattering efficiency is computed from first principles in order to univocally assign the measured Raman peaks to the calculated eigenvectors. Measured and calculated Raman spectra are shown to be in qualitative agreement and confirm the mode assignment by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)], thus finally settling a long debate. While the two crystals show rather similar vibrational properties overall, the E-TO9 mode is markedly different in the two oxides. The deviations are explained by a different anion-cation bond type in LiTaO3 and LiNbO3 crystals.

Magnetoconductance of a magnetic double barrier in a quantum wire - Schüler, B.; Cerchez, M.; Xu, Hengyi; Heinzel, T.; Reuter, Dirk; Wieck, A.D. (Superlattices and Microstructures)

Confocal shift interferometry of coherent emission from trapped dipolar excitons - Repp, J.; Schinner, G. J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Wurstbauer, U.; Kotthaus, J. P.; Holleitner, A. W. (Applied Physics Letters)

Observation of quantum states without a semiclassical equivalence bound by a magnetic field gradient - Schüler, B.; Cerchez, M.; Xu, Hengyi; Schluck, J.; Heinzel, T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Spin-flip Raman scattering of the resident electron in singly charged (In,Ga)As/GaAs quantum dot ensembles - Debus, J.; Sapega, V. F.; Dunker, D.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

All-optical implementation of a dynamic decoupling protocol for hole spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Excitation of complex spin dynamics patterns in a quantum-dot electron spin ensemble - Varwig, S.; Yugova, I. A.; René, A.; Kazimierczuk, T.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Magnetic properties of Gd-doped GaN - Shvarkov, Stepan; Ludwig, Astrid; Wieck, Andreas Dirk; Cordier, Yvon; Ney, Andreas; Hardtdegen, Hilde; Haab, Anna; Trampert, Achim; Ranchal, Rocío; Herfort, Jens; Becker, Hans-Werner; Rogalla, Detlef; et al. (physica status solidi (b))

Time and spatially resolved electron spin detection in semiconductor heterostructures by magneto-optical Kerr microscopy - Henn, Tobias; Kießling, Tobias; Molenkamp, Laurens W.; Reuter, Dirk; Wieck, Andreas D.; Biermann, Klaus; Santos, Paulo V.; Ossau, Wolfgang (physica status solidi (b))

Optically controlled initialization and read-out of an electron spin bound to a fluorine donor in ZnSe - Kim, Y.M.; Sleiter, D.; Sanaka, K.; Reuter, Dirk; Lischka, K.; Yamamoto, Y.; Pawlis, A. (Current Applied Physics)

Structural, optical, and magnetic properties of highly-resistive Sm-implanted GaN thin films - Lo, Fang-Yuh; Huang, Cheng-De; Chou, Kai-Chieh; Guo, Jhong-Yu; Liu, Hsiang-Lin; Ney, Verena; Ney, Andreas; Shvarkov, Stepan; Pezzagna, Sébastien; Reuter, Dirk; Chia, Chi-Ta; Chern, Ming-Yau; et al. (Journal of Applied Physics)

Determining the stability and activation energy of Si acceptors in AlGaAs using quantum interference in an open hole quantum dot - Carrad, D. J.; Burke, A. M.; Klochan, O.; See, A. M.; Hamilton, A. R.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Micolich, A. P. (Physical Review B)

Nuclear magnetic resonances in (In,Ga)As/GaAs quantum dots studied by resonant optical pumping - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Petrov, M. Yu.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

All-optical tomography of electron spins in (In,Ga)As quantum dots - Varwig, S.; René, A.; Economou, Sophia E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review B)

Direct Quantitative Electrical Measurement of Many-Body Interactions in Exciton Complexes in InAs Quantum Dots - Labud, P. A.; Ludwig, A.; Wieck, A. D.; Bester, G.; Reuter, Dirk (Physical Review Letters)

Non-polar GaN quantum dots integrated into high quality cubic AlN microdisks - Bürger, M.; Callsen, G.; Kure, T.; Hoffmann, A.; Pawlis, A.; Reuter, Dirk; As, D. J. (physica status solidi (c))

Manipulating wave propagation with geometric metasurfaces: fundamentals and applications - Huang, Lingling; Chen, Xianzhong; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Zentgraf, Thomas; Zhang, Shuang (Plasmonics)

Optical spectrum, perceived color, refractive index, and non-adiabatic dynamics of the photochromic diarylethene CMTE - Wiebeler, Christian; Bader, Christina A.; Meier, Cedrik; Schumacher, Stefan (Phys. Chem. Chem. Phys.)

Polarization properties of single zinc-blende GaN/AlN quantum dots - Sergent, S.; Kako, S.; Bürger, M.; Schupp, T.; As, Donat Josef; Arakawa, Y. (Physical Review B)

Radio Frequency Electromechanical Control over a Surface Plasmon Polariton Coupler - Ruppert, Claudia; Förster, Frederike; Zrenner, Artur; Kinzel, Jörg B.; Wixforth, Achim; Krenner, Hubert J.; Betz, Markus (ACS Photonics)
We explore the impact of ∼500 MHz surface acoustic waves traveling across a commensurable plasmonic grating coupler. A stroboscopic technique involving surface acoustic waves synchronized to a modelocked optical source allows to time-resolve the dynamical impact of the electromechanically induced perturbation. The surface acoustic wave periodically enhances or decreases the surface ripple of the static grating. Most remarkably, the dynamic surface deformation deliberately modulates the coupler’s efficiency by ±2% during the ∼2 ns acoustic cycle.
Keywords: nanomechanics; plasmonics; surface acoustic waves; surface plasmon polaritons

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Hochauflösende Holografie - Zentgraf, Thomas (Physik in unserer Zeit)

mm-Wellen- und Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Fakultätskolloquium der Fakultät für Elektrotechnik und Informationstechnik)

Electro-optic tuning of split ring resonators embedded in a liquid crystal - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Letters)

Effect of Alignment on a Liquid Crystal/Split-Ring Resonator Metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (ChemPhysChem)

Polycyclic Aromatic Hydrocarbons Obtained by Lateral Core Extension of Mesogenic Perylenes: Absorption and Optoelectronic Properties - Vollbrecht, Joachim; Bock, Harald; Wiebeler, Christian; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (Chemistry - A European Journal)

Polymer-stabilized blue phases: promising mesophases for a new generation of liquid crystal displays - Nordendorf, G.; Hoischen, A.; Schmidtke, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Columnar molecular aggregation in the aqueous solutions of disodium cromoglycate - Agra-Kooijman, Dena M.; Singh, Gautam; Lorenz, Alexander; Collings, Peter J.; Kitzerow, Heinz-Siegfried; Kumar, Satyendra (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Synthesis of Liquid Crystal Silane-Functionalized Gold Nanoparticles and Their Effects on the Optical and Electro-Optic Properties of a Structurally Related Nematic Liquid Crystal - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Nanoparticle Doping in Nematic Liquid Crystals: Distinction between Surface and Bulk Effects by Numerical Simulations - Urbanski, Martin; Mirzaei, Javad; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Planar anchoring strength and pitch measurements in achiral and chiral chromonic liquid crystals using 90-degree twist cells - McGinn, Christine K.; Laderman, Laura I.; Zimmermann, Natalie; Kitzerow, Heinz-Siegfried; Collings, Peter J. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Alfred Saupe Prize 2013 Laudatio for Prof. Dr Gerd Heppke* - Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Measurement of group velocity dispersion in a solid-core photonic crystal fiber filled with a nematic liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Liquid crystal assisted optical fibres - Wahle, M.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Tunable infrared resonance spectra of split ring resonators embedded in a liquid crystal - Atorf, B.; Muhlenbernd, H.; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (2013 7th International Congress on Advanced Electromagnetic Materials in Microwaves and Optics)

Photonic Micro- and Nanostructures, Metamaterials - Kitzerow, Heinz-Siegfried (Handbook of Liquid Crystals)

Real-time coherent detection of phase modulated ultrashort pulses after time-to-space conversion and spatial demultiplexing - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Three-dimensional hybrid vortex solitons - Driben, Rodislav; Kartashov, Yaroslav V.; Malomed, Boris A.; Meier, Torsten; Torner, Lluis (New Journal of Physics)
We show, by means of numerical and analytical methods, that media with a repulsive nonlinearity which grows from the center to the periphery support a remarkable variety of previously unknown complex stationary and dynamical three-dimensional (3D) solitary-wave states. Peanut-shaped modulation profiles give rise to vertically symmetric and antisymmetric vortex states, and novel stationary hybrid states, built of top and bottom vortices with opposite topological charges, as well as robust dynamical hybrids, which feature stable precession of a vortex on top of a zero-vorticity soliton. The analysis reveals stability regions for symmetric, antisymmetric, and hybrid states. In addition, bead-shaped modulation profiles give rise to the first example of exact analytical solutions for stable 3D vortex solitons. The predicted states may be realized in media with a controllable cubic nonlinearity, such as Bose–Einstein condensates.

Theory of filtered type-II parametric down-conversion in the continuous-variable domain: Quantifying the impacts of filtering - Christ, Andreas; Lupo, Cosmo; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (Physical Review A)
Parametric down-conversion (PDC) forms one of the basic building blocks for quantum optical experiments. However, the intrinsic multimode spectral-temporal structure of pulsed PDC often poses a severe hindrance for the direct implementation of the heralding of pure single-photon states or, for example, continuous-variable entanglement distillation experiments. To get rid of multimode effects narrowband frequency filtering is frequently applied to achieve a single-mode behavior. A rigorous theoretical description to accurately describe the effects of filtering on PDC, however, is still missing. To date, the theoretical models of filtered PDC are rooted in the discrete-variable domain and only account for filtering in the low-gain regime, where only a few photon pairs are emitted at any single point in time. In this paper we extend these theoretical descriptions and put forward a simple model, which is able to accurately describe the effects of filtering on PDC in the continuous-variable domain. This developed straightforward theoretical framework enables us to accurately quantify the tradeoff between suppression of higher-order modes, reduced purity, and lowered Einstein–Podolsky–Rosen entanglement, when narrowband filters are applied to multimode type-II PDC.